Corporate Mergers and Acquisitions from the Perspective of Competition Law (A Comparative Study Between Indonesia and Japan) - Yugo Rahmanto, Gumelar Taufik (MIH FH UNSOED, 2024)
This research focuses on analyzing the implementation of mergers and acquisitions from the perspective of competition law through a comparison between Indonesian and Japanese laws. By conducting legal comparisons, it is hoped that points of improvement can be obtained for competition law in Indonesia in supervising the implementation of mergers and acquisitions. The research method used is doctrinal legal research (dogmatic legal research), with a legis-positivist approach that places the law synonymous with written rules compiled and promulgated by the authorities and sees the law as a normative system that stands alone, closed, and detached from society. Through this research, the author finds that the regulation of mergers and acquisitions in Indonesia from the perspective of competition law, when compared to Japan, is much slower in development. While countries like Japan have long embraced the pre-merger notification regime, Indonesia only adopted it in 2009, and it is regulated through the KPPU Regulation on Pre-Notification of Mergers, Consolidations, and Acquisitions (2009). This certainly creates a misalignment between the Unfair Competition Prohibition Law (1999), which adopts the post-merger notification regime, and the KPPU Regulation on Pre-Notification of Mergers, Consolidations, and Acquisitions (2009). Through this research, the author suggests that harmonization and synchronization between the post-merger notification approach adopted by the Unfair Competition Prohibition Law (1999) and the pre-merger notification approach adopted by the KPPU Regulation on Pre-Notification of Mergers, Consolidations, and Acquisitions (2009) are necessary. This is to avoid confusion among business actors and legal uncertainty that may distort the market.